Active vibration isolation for free space optics (FSO) communication using electromagnetic actuator - Khairiah Kamilah Bt. Turahim (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
A free space optics (FSO) communication link which consists of a transmitter and a receiver FSO link head is used in transmission of data. The transmitter and receiver must be continuously aligned in order to successfully transmit data. Unfortunately, due to certain factors, the transmitter and receiver fail to have a continuous alignment resulting in misalignment that will effect transmission of data. Amongst the factors that cause misalignment include vibration either at the transmitter or receiver. In this work, an active vibration isolation system is proposed to actively isolate low frequency vibration from the surrounding environment of the transmitter and receiver mounting location which is usually located on rooftops or on top of high rise buildings. Before developing a real prototype of the active vibration isolation system, a virtual prototype is developed to observe the performance of the active vibration isolation test rig. Then, a real prototype is constructed which consists of an active vibration isolation test rig, a vibration exciter mechanism, a force generating actuator, sensors, and electronic controllers. Furthermore, it is necessary to design a controller to suppress the unwanted vibration by controlling the actuator force. Different controllers have been implemented in the system which include the simple gain feedback controller, Proportional Integral Derivative (PID) controller and Linear Quadratic Regulator (LQR) controller. The effectiveness of the controllers are evaluated through simulations and experiments on the lab-scale active vibration isolation system. The results are obtained by observing the peak amplitude of displacement and peak amplitude of frequency of the top plate of the active vibration isolation system. The proposed controllers are able to reduce vibration at excitation frequency of 9 Hz, the chosen frequency based on literature; the peak amplitude of displacement has been reduced by 34.31% using PID controller and 36.76% using LQR controller.